Fresno County Bar Association Legislators' Reception at The Downtown Club - Watkins, Howard::::::::: (1988)
Mildred Christian shaking hands with State Assemblymember Bruce Bronzan Seated: Linda Bankston and Rhalene Kimberly; Standing: Jean Lewis